Haematological adaptations to high-altitude and heat acclimation training in elite male cyclists - Cubel, C.; Klaris, M. B.; Larsen, J. V.; Faiss, R.; Nybo, L.; Lundby, C. (Experimental Physiology, 2026)
High-altitude training is widely adopted by endurance athletes with the aim of increasing total haemoglobin mass (tHbmass) and thereby endurance exercise performance. However, divergent effects on tHbmass and exercise performance have been reported in athletes commencing altitude camps with initial high baseline levels for tHbmass, questioning the efficacy of in-season interventions in elite athletes. Therefore, haematological adaptations and exercise performance were evaluated in 12 elite cyclists completing an in-season `Live High-Train High` (LHTH) altitude camp (21 days at 3000 m) immediately after participating in the national championships. Additionally, for seven participants, we compared haematological and exercise performance effects with an off-season heat acclimation training (HEAT) intervention (six 1-h sessions per week for 5 weeks). The LHTH resulted in a 3.5 ± 2.0% (P < 0.001, n = 12) increase in tHbmass, with decay to Pre levels 10 days after returning to sea-level. For participants followed for 9 months, the tHbmass effect was comparable to that of the off-season HEAT intervention (5.4 ± 3.9% for HEAT, LHTH vs. HEAT: P = 0.801, n = 7) and baseline levels prior to the interventions were almost identical (965 g Pre-HEAT vs. 960 g Pre-LHTH). Exercise performance and maximal oxygen uptake, tested immediately (2-3 days) and 10 days after LHTH, were not improved, and individual changes were not correlated to any of the haematological parameters assessed. In conclusion, the in-season LHTH training camp effectively increased tHbmass in elite cyclists; however, there was a rapid decay in tHbmass upon return to sea-level and no effect on exercise performance.